2013
DOI: 10.1073/pnas.1304903110
|View full text |Cite
|
Sign up to set email alerts
|

Control of cell proliferation, endoreduplication, cell size, and cell death by the retinoblastoma-related pathway in maize endosperm

Abstract: The endosperm of cereal grains is one of the most valuable products of modern agriculture. Cereal endosperm development comprises different phases characterized by mitotic cell proliferation, endoreduplication, the accumulation of storage compounds, and programmed cell death. Although manipulation of these processes could maximize grain yield, how they are regulated and integrated is poorly understood. We show that the Retinoblastoma-related (RBR) pathway controls key aspects of endosperm development in maize.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(94 citation statements)
references
References 67 publications
(94 reference statements)
2
92
0
Order By: Relevance
“…S2). (Sabelli et al, 2013). Related to that, we found seven minichromosome maintenance transcripts that control DNA duplication (Chong et al, 1996;Aparicio et al, 1997), which are known targets of E2F transcription factors (Vandepoele et al, 2005), and four transcripts of genes encoding subunits of the anaphase-promoting complex (APC) that controls the cell cycle at M-phase exit (Eloy et al, 2006).…”
Section: Cell Cycle Regulationmentioning
confidence: 53%
“…S2). (Sabelli et al, 2013). Related to that, we found seven minichromosome maintenance transcripts that control DNA duplication (Chong et al, 1996;Aparicio et al, 1997), which are known targets of E2F transcription factors (Vandepoele et al, 2005), and four transcripts of genes encoding subunits of the anaphase-promoting complex (APC) that controls the cell cycle at M-phase exit (Eloy et al, 2006).…”
Section: Cell Cycle Regulationmentioning
confidence: 53%
“…Furthermore, retinoblastoma-related protein genes RBR1 and RBR2 were highly expressed in sperm cells ( Figure 6A, SP versus all: log 2 FC > 2.9*). RBR1 and RBR2 mediate G1-phase arrest by inhibiting E2F TFs, which in turn promote DNA replication (Sabelli et al, 2013). Compared with the other cell types, egg cells showed by far the lowest expression levels of cell cycle genes and lacked a typical cell cycle phase-specific gene expression pattern.…”
Section: Cell Cycle Regulation During Zygote Developmentmentioning
confidence: 99%
“…At cell and tissue levels, several investigations have characterized specific physiological processes during kernel development (Borrás and Gambín 2010;Ettenhuber et al 2005;Sabelli et al 2013;Young and Gallie 2000) and identified the influence of water deficit (Ober et al 1991;Setter and Flannigan 2001) and genotype (Jones et al 1996) on this process. At the plant canopy level, a number of studies have described the special physiological process (Blewley and Black 1985), source-sink interactions (Borrás et al 2004;Gambin et al 2006;Jones and Simmons 1983), kernel growth-plant growth interactions (Gambin et al 2008), and the effect of dynamic water content during kernel development (Borrás and Westgate 2006;Westgate 1994;Westgate and Boyer 1986).…”
Section: Introductionmentioning
confidence: 99%